Application of three-dimensional-printed porous tantalum cones in total knee arthroplasty revision to reconstruct bone defects - Ao, Yunong; Guo, Lin; Chen, Hao; He, Rui; Yang, Pengfei; Fu, Dejie; Gu, Lingchuan; Peng, Yang; Xiong, Ran; Yang, Liu; Wang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Three-dimensional (3D) printing technology has emerged as a new treatment method due to its precision and personalization. This study aims to explore the application of a 3D-printed personalized porous tantalum cone for reconstructing the bone defect in total knee arthroplasty (TKA) revision. Methods: Between November 2017 and October 2020, six patients underwent bone reconstruction using 3D-printed porous tantalum cones in TKA revision. The knee function was assessed using the Hospital for Special Surgery (HSS) score pre- and postoperatively. The pain was measured by the visual analog scale (VAS) pre- and postoperatively. The quality of life was measured using the 36-Item Short Form Health Survey (SF-36) to pre- and postoperatively evaluate the relief of pain. Operation time, intraoperative blood loss, postoperative drainage volume, and complications were also recorded. At the last follow-up, all patients received X-ray and computed tomography (CT) to confirm the effect of bone reconstruction. Results: After an average follow-up duration of 26.3 months, no patients developed any operation-related complications. The average intraoperative blood loss and postoperative drainage volumes were 250.1 ± 76.4 ml and 506.7 ± 300.8 ml, respectively. At the last follow-up, the HSS score was significantly higher than that before operation, indicating that the knee function was significantly improved (p < 0.001). During the follow-up, the mean VAS score decreased and the mean SF-36 score increased, both of which were significantly improved compared with preoperative conditions (p < 0.001). Radiological examination at the final follow-up showed that cones implanted into the joint were stable and bone defects were effectively reconstructed. Conclusion: This study demonstrated that 3D-printed porous tantalum cones could effectively reconstruct bone defects and offer anatomical support in TKA revision. Further studies are still needed to confirm the long-term effect of 3D-printed tantalum cones for reconstructing bone defects.